Gangguan fungsi Jantung pada Keadaan Sepsis - Kabul Priyantoro; Soroy Lardo; Yoga Yuniadi (The Indonesian Heart Association, 2010)
Sepsis is a condition where bacteremia persist and precede by SIRS sign, in a severe condition sepsis can manifest as septic shock and refractory septic shock with very high mortality rate, up to 50% during hospitalization, almost equalize death due to myocardial infarction. In a severe sepsis at least one of organ dysfunction is present, cardiovascular is one of the most frequent affected organ system in severe sepsis and almost always affected during septic shock. During sepsis depression of cardiac systolic and diastolic func-tion characterized by bi-ventricular impairment of contractility, decrease in ventriclular compliance which manifest as subsequent reduction in left ventricular ejection fraction and LV stroke work index. The pathophysi-ology of cardiac depression during sepsis remain unclear up to now, but many evidence showed that circulating cardio toxic agent (IL – 1, IL – 8, C3a), endotoxin (LPS), cytokine (IL – 1, IL – 6, TNF – a), endothelin – 1 (ET – 1), nitric oxide (NO), prostanoid (Tromboxan & Prostasiklin), and adhesion molecule (intercellular adhesion molecule-1 & vascular cell adhe-sion molecule-1) play important role in depressing cardiac function during sepsis. Definitive therapy regarding cardiac dysfunction during sepsis is still unknown, but adequate supportive management in maintaining adequate preload continued by inotropic and or vasopressor with low dose cor-ticosteroid, low dose nitroglycerine (in selected patients) and statin are prove in clinical trial effective in providing better outcome. Poor cardiac function in sepsis is related to poor outcome during hospitalization. This article discus about cardiac dysfunction, pathophysiology and supportive management in adult with sepsis.